METHODS OF TREATMENT OF CONGENITAL HEART DEFECTS IN MODERN MEDICINE - Tolmasov Ruzibek Tolmasovich; Turabov Lazizjon Narimon o‘g‘li (Western European Studies, 2024)
The purpose of this article is to describe congenital heart defects, to study their causes and to provide information about accurate and rapid diagnostic diagnosis and treatment methods of these defects with the help of improved devices available in modern medicine .
Keywords: echocardiography; Doppler echocardiography; Exo-KG; Doppler-echo-KG